Skæg og blå briller i Nordens Casablanca. Det svenske sikkerhedspolitis overvågning af Ebbe Munck i Stockholm under 2. Verdenskrig - Nielsen, Jacob Vrist (Historisk Tidsskrift, 2024)
Cloak-and-dagger in the Casablanca of the North: Swedish security surveillance of Ebbe Munck in Stockholm during World War II During World War II, the Swedish Security Police monitored thousands of foreigners in the Swedish capital, Stockholm. One of them was the Danish reporter and patriot Ebbe Munck (1905–74). Drawing on archival material from Denmark, Sweden and Great Britain, this article investigates how the Swedish Security Police conducted the surveillance of Ebbe Munck and why he was being monitored. In addition, the article examines the effectiveness of the Swedish surveillance, including the extent to which Munck knew he was being monitored. This surveillance was ineffective and unprofessional, which was typical at the time: The Swedish Security Police had spied on the British legation in the same amateurish way. Stockholm, known by some as „the Casablanca of the North“, overflowed with spies, and the Security Police was in its formative stage and tried to monitor all of them despite its limited resources. Furthermore, the article shows that Ebbe Munck knew he was being watched. However, he was wrong about the timing, character and reasons for the Swedes’ surveillance. In general, Munck was as clumsy at discovering the surveillance as the Swedish Security Police was at conducting it.